Role of land use planning in improving public health: way forward for Malaysia - Maidin, Ainul Jaria (IIUM Press, 2009)
This research seeks to identify the ways in which land use planning system can be used to improve public health in Malaysia. the present state of Malaysian environment has been deteriorating owing to the priority accorded to economic development is rather worrying. This study seeks to examine the role assumed by the land planning and development process in improving public health. The research also seeks to identify the improvements that can be made to the Malaysian land use planning and development process as a means of improving public health.